Gamma knife radiotherapy of brain metastasis resection cavities: outcome analysis of a single-center cohort - Jiménez, Àlex Godó; Wieger, Gero; Brehmer, Stefanie; Abo-Madyan, Yasser; Stieler, Florian; Giordano, Frank Anton; Ruder, Arne Mathias (Anticancer research, 2025)
Background/Aim: Stereotactic radiotherapy (SRT), including stereotactic radiosurgery (SRS) and fractionated stereotactic radiotherapy (FSRT), is the current standard adjuvant treatment after resection of brain metastases (BM). In the era of immunotherapy and targeted systemic therapies enabling effective extracranial control, achieving durable intracranial outcomes has become increasingly important. Intraoperative radiotherapy (IORT) is an emerging alternative to Gamma Knife-based irradiation. We aimed to assess the clinical outcome of BM resection cavities treated with Gamma Knife SRT (GK-SRT), for retrospective comparison to a cohort treated with IORT. - Patients and Methods: This retrospective single-center analysis included all patients who received GK-SRT to the resection cavity after complete surgical removal of BM. A total of 41 cavities from 37 patients were evaluated. Local control (LC), distant intracranial control (DIC), and overall survival (OS) were calculated, and the potential influence of whole-brain radiotherapy (WBRT) as part of the adjuvant treatment on OS was analyzed. - Results: With a median follow-up of 19.3 months, the 1-year LC was 93.3%. The 1-year DIC was 54.1%, and the median OS was 27.3 months. Median cavity volume was 5.89 cm3; the median interval from surgery to GK-SRT initiation was 24.5 days, and to subsequent systemic treatment 59.0 days. DIC, but not LC, was significantly associated with OS, with better DIC correlating with longer survival. WBRT as part of the adjuvant regimen did not confer a significant survival benefit. - Conclusion: Adjuvant GK-SRT to the resection cavity is an effective treatment with excellent local control. Nonetheless, challenges remain regarding distant intracranial progression and overall survival.